2009
DOI: 10.1590/s1020-49892009001000007
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization of visceral leishmaniasis (kala-azar) in Fortaleza, Ceará, Brazil

Abstract: The epidemic occurrence of VL in the region must convince authorities to adopt more adequate policies of disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 11 publications
3
20
0
8
Order By: Relevance
“…The minimum age was 5 years and maximum age was 70 years, which was consistent with results of other studies in Brazil, but were less than those of India (mean age, 45 years) [6,14,15]. Sixty-one patients (44.2%) were males, and the mean age was 29.65±11.10 years, which come in line with others [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The minimum age was 5 years and maximum age was 70 years, which was consistent with results of other studies in Brazil, but were less than those of India (mean age, 45 years) [6,14,15]. Sixty-one patients (44.2%) were males, and the mean age was 29.65±11.10 years, which come in line with others [15].…”
Section: Discussionsupporting
confidence: 91%
“…The rest of the patients were females with a mean age of 26.12±11.89 years, minimum age of 5 years, and maximum age of 70 years, which was contrary to results of an Indian study indicated that 93% of affected patients were males. In Brazil, 65% of Kala -azar patients were males and in Ethiopia they represents (74%-85.6%) [6,[14][15][16]. High male patient load could be because of the economic activities that entail sex bias.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature influences the growth of sand flies (Cross and Hyams 1996), a factor that has gained importance with the increase in global temperature (Hemmer et al 2007). Overall these changes have resulted in the widening of VL endemic areas in Brazil (Costa et al 1990, Jeronimo et al 1994, Marzochi et al 1994, Nascimento et al 1996, Albuquerque et al 2009). …”
mentioning
confidence: 99%
“…Currently most Brazilian states report autochthonous cases of VL, which was previously limited to northern and northeastern states, but it has now been reported as far south as northern Argentina (Costa et al 1990, Jeronimo et al 1994, Marzochi et al 1994, Nascimento et al 1996, Salomon et al 2008, Albuquerque et al 2009). The pattern of VL in Natal, Rio Grande do Norte, northeast Brazil, provides an example of the periurbanization of leishmaniasis.…”
mentioning
confidence: 99%
“…1,2 Over the past 30 years, numerous outbreaks have been reported from Natal and other major cities in Brazil. [3][4][5][6][7] These outbreaks have coincided with large-scale migration of people, with their dogs and other domestic animals, from rural areas endemic for L. i. chagasi to urban areas. 8 In turn, the city of Natal itself has expanded into previously rural endemic areas.…”
Section: Introductionmentioning
confidence: 99%